Некоторые aспекты соглaшений о сотрудничестве между Египтом и Сaудовской Aрaвией - Әліпбaев А. (International relations and international law Journal, 2018)
Article is devoted to a cooperation between Egypt and Saudi Arabia. After the revolution in 2011 state of the economy of Egypt worsened. Cairo tries to accelerate growth, including by means of foreign investments. In April, 2016 Egypt and Saudi Arabia signed a number of documents on a cooperation in various areas. For implementation of the planned projects Egypt and Saudi Arabia approved delimitation of sea border between the states therefore the disputed islands which were under the administration of Cairo the Tyrant and Sanafir in the Red Sea departed to Riyadh. Besides, the agreement on creation of a joint investment fund with the equity of 16 billion dollars was reached. The arrangement between Sisi and Salman about the bridge construction through the Red Sea connecting the territories of two countries became sensational. According to leaders of two countries, this bridge «will become in the way to implementation of perspective projects between Egypt and Saudi Arabia». Key words: Egypt, Saudi Arabia, investment, economy, foreign policy, national security.